Branding Strategy and Challenge the Tourism in Jayapura Regency - M. Zaenul Muttaqin; Oscar Oswald O. Wambrauw (Formosa Journal of Applied Sciences, 2023)
This research is aimed at gathering information and analyzing branding strategies to strengthen the tourism image of Jayapura Regency. This study uses a descriptive qualitative approach, namely describing and analyzing branding strategies to strengthen the tourism image of Jayapura Regency. Sources of data in this study came from the website belonging to the Jayapura Regency Culture and Tourism Office, online news related to the theme, and literature reviews. The data analysis technique used in this study refers to that described by Creswell in Moleong (2008), namely using 5 steps, namely: processing and preparing data for analysis, reading the entire data, analyzing in more detail by coding the data. Based on the results of this study, tourism branding in Jayapura Regency has several challenges.